St. Mary's Collegiate Church, Youghal, south choir wall, sedilia, jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
Jamb, arch and hood moulding of sedilia. From intrados moulding comprises: ogee roll-and-fillet, quadrant, double ogee. The hood, from the outer to inner face reads: chamfer, ogee, hollow chamfer, ogee. This is an unusual moulding, in scale and in variety of elements. It resembes the west door moulding of Abbeydorney Cistercian Monastery and these buildings may be linked by the patronge of the Earl of Desmond.
Sedilia
Keywords: quadrant; Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Youghal (Cork, Ireland); Benedictine architecture; Late Medieval; moldings, ogee; moldings, hollow; fillets (moldings); roll moldings; roll-and-fillet moldings; hood moldings